Governance of State Owned Enterprises and Public Agencies in the Islamic Republic of Mauritania - World Bank (Washington, DC, 2015)
This study analyzes the governance framework of the business portfolio of Mauritanian institutions and government agencies and offers avenues for reform. The report begins with an overview of the scope of work and performance of the portfolio mentioned using the term Para-Statal sector and identifies the main challenges represented by this sector. It then analyzes the governance framework of Para-statal sector of Mauritania through comparative references from the guidelines of the OECD. The diagnosis includes an analysis of the legal framework, the supervisory function, risk monitoring budget and performance in terms of delivery of services, advice to administration, transparency and dissemination of information. The report closes with a detailed and sequenced action plan compiled from observations in the diagnosis and offers a series of suggestions for appropriate reforms to the institutional context of Mauritania. The action plan focuses primarily on strengthening the monitoring of risk of the budget and proposes ways of sequenced reforms taking into account both international examples and the Mauritanian context.